Risk factors for chronic ankle instability after first episode of lateral ankle sprain: A retrospective analysis of 362 cases - Jieyuan Zhang; Kai Yang; Cheng Wang; Wenqi Gu; Xueqian Li; Shaoling Fu; Guoxun Song; Jiazheng Wang; Chenglin Wu; Hongyi Zhu; Zhongmin Shi (Elsevier, 2023)
Background: Chronic ankle instability (CAI) is a common sequela following an acute lateral ankle sprain (LAS). To treat an acute LAS more effectively and efficiently, it is important to identify patients at substantial risk for developing CAI. This study identifies magnetic resonance imaging (MRI) manifestations for predicting CAI development after a first episode of LAS and explores appropriate clinical indications for ordering MRI scans for these patients. Methods: All patients with a first-episode LAS who received plain radiograph and MRI scanning within the first 2 weeks after LAS from December 1, 2017 to December 1, 2019 were identified. Data were collected using the Cumberland Ankle Instability Tool at final follow-up. Demographic and other related clinical variables, including age, sex, body mass index, and treatment were also recorded. Univariable and multivariable analyses were performed successively to identify risk factors for CAI after first-episode LAS. Results: A total 131 out of 362 patients with a mean follow-up of 3.0 ± 0.6 years (mean ± SD; 2.0-4.1 years) developed CAI after first-episode LAS. According to multivariable regression, development of CAI after first-episode LAS was associated with 5 prognostic factors: age (odds ratio (OR) = 0.96, 95% confidence interval (95%CI): 0.93-1.00, p = 0.032); body mass index (OR = 1.09, 95%CI: 1.02-1.17, p = 0.009); posterior talofibular ligament injury (OR = 2.17, 95%CI: 1.05-4.48, p = 0.035); large bone marrow lesion of the talus (OR = 2.69, 95%CI: 1.30-5.58, p = 0.008), and Grade 2 effusion of the tibiotalar joint (OR = 2.61, 95%CI: 1.39-4.89, p = 0.003). When patients had at least 1 positive clinical finding in the 10-m walk test, anterior drawer test, or inversion tilt test, they had a 90.2% sensitivity and 77.4% specificity in terms of detecting at least 1 prognostic factor by MRI. Conclusion: MRI scanning is valuable in predicting CAI after first-episode LAS for those patients with at least 1 positive clinical finding in the 10-m walk test, anterior drawer test, and inversion tilt test. Further prospective and large-scale studies are necessary for validation.